Exploring lecturer experiences of the use of ICT in blended learning : a case study at a South African university - Ntlabathi, Siyanda (Rhodes University, Faculty of Education, Department of Education, 2015)
ICTs have had a tremendous impact on our educational environment. There have been a huge number of developments and support in implementation of ICT in Higher Education teaching and learning, also referred to as e-learning. Similarly there appears to be quite a number of research conducted on the use of ICTs in blended learning settings worldwide and as well as in South Africa. Very little research however, has focussed on the experiences of lecturers with e-learning, specifically as it relates to Learning Management Systems (LMS). In trying to meet the requirements of its academic programmes and be in line with new developments worldwide, the University which is the focus of this study pilot projected the use of an LMS in a blended learning approach which integrates face-to-face classes with Blackboard, an ICT-based system or tool. Following the implementation of the pilot project, this study explores the experiences of lecturers in their blended learning environments at this university in the Eastern Cape province of South Africa. The research design was that of an interpretative paradigm within a qualitative research approach in a case study methodology. Purposive sampling of six lecturers from departments within faculties across two campuses was done. The data was gathered through interviews, a follow-up questionnaire and document analysis was employed. Using Critical and Social Realism as meta-theories the study employed aspects of Activity Theory as substantive theory to understand particular experiences of blended learning environments and identify conditions which enable and constrain engagement in these environments so as to explore potential lessons to inform the kind of educational support which could be offered to facilitate uptake of the LMS.
Keywords: Blended learning -- South Africa; Information technology -- South Africa; Education, Higher -- Technological innovations; Computer-assisted instruction -- South Africa; Internet in education -- South Africa; Educational technology -- South Africa; Critical realism